Glycogen synthase kinase 3 inhibition enhances mineral nodule formation by cementoblasts in vitro - Henrique ABDALLA; Rafael STORINO; Amanda BANDEIRA; Lucas TEIXEIRA; Ana MILLÁS; Paulo LISBOA-FILHO; Kamila KANTOVITZ; Francisco NOCITI JUNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aimed to investigate whether GSK-3 inhibition (CHIR99021) effectively promoted mineralization by cementoblasts (OCCM-30). OCCM-30 cells were used and treated with different concentrations of CHIR99021 (2.5, 5, and 10 mM). Experiments included proliferation and viability, cellular metabolic activity, gene expression, and mineral nodule formation by Xylene Orange at the experimental time points. In general, CHIR99021 did not significantly affect OCCM-30 viability and cell metabolism (MTT assay) (p > 0.05), but increased OCCM-30 proliferation at 2.5 mM on days 2 and 4 (p < 0.05). Data analysis further showed that inhibition of GSK-3 resulted in increased transcript levels of Axin2 in OCCM-30 cells starting as early as 4 h, and regulated the expression of key bone markers including alkaline phosphatase (Alp), runt-related transcription factor 2 (Runx-2), osteocalcin (Ocn), and osterix (Osx). In addition, CHIR99021 led to an enhanced mineral nodule formation in vitro under both osteogenic and non-osteogenic conditions as early as 5 days after treatment. Altogether, the results of the current study suggest that inhibition of GSK-3 has the potential to promote cementoblast differentiation leading to increased mineral deposition in vitro.